The boys in the boat [videorecording (Blu-Ray)] - Smith, Mark L.; Edgerton, Joel, 1974-; Turner, Callum, 1990-; Guinness, Peter, 1950-; Mulhern, Jack, 1994-; Wolk, James; Robinson, Hadley (Actress); Henggeler, Courtney, 1978-; Brown, Daniel James, 1951- (Warner Bros. Entertainment Inc., 2024)
Based on the non-fiction book written by Daniel James Brown, and directed by George Clooney, this is the story of the 1936 University of Washington rowing team that competed for gold at the Summer Olympics in Berlin. This inspirational true story follows a group of underdogs at the height of the Great Depression as they are thrust into the spotlight and take on elite rivals from around the world.